Stereocontrolled syntheses of (−)- and (+)-γ-diisoeugenol along with optically active eight stereoisomers of 7, 8′-epoxy-8, 7′-neolignan. Issue 10 (24th February 2021) - Takubo, Tatsuaki; Kikuchi, Nao; Nishiwaki, Hisashi; Yamauchi, Satoshi
Abstract : It was shown that reduction of the tertiary benzylic hydroxy group of 3-furanol followed by the intramolecular Friedel–Crafts reaction gave exclusively indane structure along with 7, 8′-epoxy-8, 7′-neolignan structure. Abstract : It was shown that reduction of the tertiary benzylic hydroxy group of (2 R, 3 S, 4 R, 5 S )-3, 5-bis(4-benzyloxy-3-methoxyphenyl)-2, 4-dimethyltetrahydro-3-furanol 17 followed by the intramolecular Friedel–Crafts reaction gave exclusively indane with (7 S, 7′ S, 8 R, 8′ R )-2, 7′-cyclo-7, 8′-neolignan structure 18 along with (7 S, 7′ R, 8 S, 8′ R )-7, 8′-epoxy-8, 7′-neolignan structure 19 . Indane 18 was converted to (−)-γ-diisoeugenol ((−)-4 ). On the other hand, (2 S, 3 R, 4 R, 5 S )-3, 5-bis(4-benzyloxy-3-methoxyphenyl)-2, 4-dimethyltetrahydro-3-furanol 22 did not afford indane, but the tetrahydrofuran structure with (7 S, 7′ S, 8 S, 8′ S )-7, 8′-epoxy-8, 7′-neolignan structure 23 and 7′- epi -23 .